2018
DOI: 10.1038/s41409-018-0405-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced intensity vs. myeloablative conditioning with fludarabine and PK-guided busulfan in allogeneic stem cell transplantation for patients with AML/MDS

Abstract: Conditioning regimens contribute significantly to outcomes following allogeneic stem cell transplantation (allo-SCT). Reduced-intensity conditioning (RIC) regimens provide lower toxicity at the cost of reduced efficacy compared with myeloablative conditioning (MAC) regimens. However, because pre-transplant prognostic variables often determine the conditioning regimen, studies of RIC vs. MAC have been inconclusive. We present a retrospective analysis of 242 acute myeloid leukemia (AML) or myelodysplastic syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Several recent studies exploring high-risk populations support those findings [8,10], including a recent analysis by Veltri et al [13] evaluating HCT in high-risk AML patients age 65 years. A recent analysis by Gilleece et al [14] confirmed no difference between MAC and nonmyeloablative (NMA) conditioning/RIC, except in AML patients age <50 years with positive minimal residual disease (MRD), a population that benefited from MAC over RIC/NMA.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Several recent studies exploring high-risk populations support those findings [8,10], including a recent analysis by Veltri et al [13] evaluating HCT in high-risk AML patients age 65 years. A recent analysis by Gilleece et al [14] confirmed no difference between MAC and nonmyeloablative (NMA) conditioning/RIC, except in AML patients age <50 years with positive minimal residual disease (MRD), a population that benefited from MAC over RIC/NMA.…”
mentioning
confidence: 79%
“…In this issue, Solh et al [3] present an original analysis evaluating the impact of conditioning intensity on different disease risk index (DRI) groups of patients with AML and MDS. Although this is the first retrospective analysis to evaluate outcomes based on the DRI, numerous other investigations have addressed how best to use MAC versus less intensive conditioning strategies, with somewhat conflicting results [2,[4][5][6][7][8][9][10]. Solh et al sought to determine whether the conditioning regimen intensity impacted outcomes in patients when stratified by the DRI.…”
mentioning
confidence: 99%
“…The reduced-intensity conditioning (RIC) was offered to older patients and to those with increased comorbidities [ 77 ]. Subsequent clinical studies comparing MAC and RIC showed no significant difference in overall survival (OS) between MAC and RIC groups [ 78 , 79 ].…”
Section: Thymic Involution and Effect On Interferon-producing Cellsmentioning
confidence: 99%
“…The leukemia-free survival and non-relapse mortality also did not differ significantly between the compared groups. Moreover, the cumulative incidence of chronic GVHD and all types of infectious complications were less frequent with RIC than with MAC [ 78 , 79 ]. Avetisyan et.…”
Section: Thymic Involution and Effect On Interferon-producing Cellsmentioning
confidence: 99%